(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2019)
Perforations are significant iatrogenic complications of endodontic treatment and could lead to endodontic failure. The prognosis is generally excellent if the problem is well-diagnosed and repair is well-performed with a material that can provide proper sealing ability and biocompatibility. In this case report, the patient presented with the complaint of continuous dull pain in his right mandibular first molar tooth. The tooth was attempted for endodontic treatment and perforation has occurred at that time. Radiographic examination revealed, destruction in the furcal area with a little radiolucency and periradicular lesion involving apical region of the roots. Considering the above conditions, endodontic treatment and nonsurgical repair of furcal perforation with mineral trioxide aggregate followed by permanent restoration was planned and performed successfully. Follow up after one month, the patient was symptomless and the affected area was found healthy. However, long term clinico- radiographic follow-up is essential. Journal of Armed Forces Medical College Bangladesh Vol.11(2) 2015: 84-88